Understanding parents’ decision-making on participation in clinical trials in children’s heart surgery: a qualitative study - Clare J Taylor; Timothy J Jones; Nigel E Drury; Julie C Menzies; Anna C Lavis (BMJ Open, 2021)
Objectives Few children undergoing heart surgery are recruited to clinical trials and little is known about the views and attitudes of parents towards trials. This study explored parents’ perspectives on decision-making about their child’s participation in a clinical trial during their elective cardiac surgery.Design Qualitative interview study.Setting Single-centre substudy of a multicentre, double-blind, randomised controlled trial to investigate the effects of remote ischaemic preconditioning in children undergoing cardiac surgery.Participants Parents of children approached to participate in the trial, both consenters and decliners.Methods Semistructured interviews were conducted face-to-face or by telephone following discharge, digitally audio-recorded, transcribed and thematically analysed.Results Of 46 patients approached for the trial, 24 consenting and 2 declining parents agreed to participate in an interview (21 mothers, 5 fathers). Parental decision-making about research was influenced by (1) potential risks or additional procedures; (2) personal benefit and altruism for the ‘cardiac community’; (3) information, preparation, timing and approach; and (4) trust in the clinical team and collaboration with researchers. All of these were placed within the context of their understanding of the trial and knowledge of research.Conclusions Parents of children undergoing cardiac surgery attach value to clinical research and are supportive of clinical trials when there is no or minimal perceived additional risk. These findings enhance our understanding of the factors that influence parents’ decision-making and should be used to inform the design and conduct of future paediatric surgical trials.Trial registration number ISRCTN12923441; Pre-results.